Криза сенсу як переломний момент життя людини - Чуйко, Галина (Кам’янець-Подільський : Аксіома, 2019)
The article is devoted to the theoretical analysis of the phenomenon of crisis of the meaning of life, its peculiarities, manifestations and consequences for life of the personality, as well as hardiness as a possible barrier to the acute and prolonged human experience of the crisis of the meaning of life (similarly to coping the stress and transforming it into the possibility of learning lessons from its passing and personal growth).It is noted that the crisis of the meaning of life is the most important event on the life path of the personality, it is experienced particularly acute, because of the power of influence on a person, his / her further life and the possible catastrophic consequences, although it occurs less often than other personal crises.The views on the crisis of the meaning of life and its specifics of famous foreign psychologists (F. Ye. Vasiliuk, K. V. Karpinskyi, S. Maddi, V. Frankl, V. E. Chudnovsky, I. Yalom etc.) were considered. It is noted that what V. Frankl called the experience of an existential vacuum with its corresponding conse-quences, I. Yalom – a crisis of meaning or a crisis of senselessness, and S. Mad-dy – a «small death» or existential neurosis, K.V. Karpinskyi uses the name of the crisis of the meaning of life, which is understood as a semantic crisis in the development of personality, which blocks primarily the semantic regulation and processes of creation of sense of the individual life path and defines its main manifestations, the reason for which are the problems of searching or realizing of the meaning of life of personality. It is revealed that the crisis of the meaning of life is experienced by a human as a long and / or sharp internal conflict between the desirable (vi-tally necessary, super important for him) and objectively possible event. At this time, the man, even imagining the way to achieve the desire, can’t always use it, this makes him/her accept everything as it is, and try to cope with the situation. It is impossible to separate internal and external causes, in the expe-riencing the crisis of the meaning of life, since it is always experienced at the subjective level.It is concluded that hardiness can be used to overcome the crisis of the meaning of life of the personality, minimizing its negative consequences and transforming it into the possibility of personality’s development through learning of life lessons and finding a new personal sense of life
Keywords: crisis of the meaning of life, hardiness, meaning of life, com-mitment, existential neurosis, crisis of senselessness.